2019
DOI: 10.21037/atm.2019.11.77
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of insulin refusal and psychological insulin resistance among Korean patients with type 2 diabetes mellitus

Abstract: Background: This study investigated the prevalence of insulin refusal and compared the level of psychological insulin resistance (PIR) with the intention to accept insulin therapy among Korean patients with type 2 diabetes.Methods: Type 2 diabetes patients (n=1,209) were recruited from inner city outpatient diabetes clinics in 2016. Patient demographic, insulin recommendation, diabetes treatment type, intention to receive insulin therapy, and PIR information was collected using self-reports. The patients were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 20 publications
1
12
0
5
Order By: Relevance
“…The prevalence of PIR in males was higher than in females in our study, but the difference was not statistically significant. Moreover, another Korean study[ 23 ] found significantly higher prevalence of insulin refusal in males compared to females, results which are similar to our study results. However, the reverse is true in the American study in which females were more unwilling for insulin than males.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The prevalence of PIR in males was higher than in females in our study, but the difference was not statistically significant. Moreover, another Korean study[ 23 ] found significantly higher prevalence of insulin refusal in males compared to females, results which are similar to our study results. However, the reverse is true in the American study in which females were more unwilling for insulin than males.…”
Section: Discussionsupporting
confidence: 92%
“…One-third of the participants in our study expressed their unwillingness to use insulin. Globally, in similar studies done in the USA,[ 20 ] Netherland[ 21 ] Kenya[ 22 ] and Korea[ 23 ] the prevalence of PIR have been found to be from 30% to 83%. However, a study done on the Bangladeshi population in East London found a comparatively lower level of refusal for insulin injection among the type 2 diabetic patients.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Insulin injection refusal or psychological insulin resistance is a challenge when initiating insulin therapy. The prevalence of insulin injection refusal is diverse in different settings, ranging from 33% to 74% of patients [19][20][21][22][23]. A systematic review of 25 research articles indicated the barriers to insulin injection initiation, including patient-related factors, healthcare professional factors, and system factors [24].…”
Section: Introductionmentioning
confidence: 99%